ENTREPRENEURSHIP EDUCATIONS OF PRISON INMATESIN NIGERIA: EFFECTS ON SKILLS ACQUISITION FOR SELF RELIANCE - Ime Robson Nseobot; Anietie Imo Effiong (International Journal of Organizational Business Excellence, 2019)
The study examined the entrepreneurship educations of prison inmates’ in Nigeria: effects on skills acquisition for self reliance. The research design for this study is an Expost Facto design. The population of the study is put at 5629 according to records of the Nigerian Prisons Service, Akwa Ibom State. Simple random sampling technique was used to select 303 respondents out of the population.From the findings of the study, it was revealed that relationship between entrepreneurship educations and skills acquisition for self-reliance among Prison Inmates in Akwa Ibom Statehave a proportional effect on their skills acquisitions. Thesewill become a source of their livelihood after completing their jail terms, foster quickly integration into the labour market and the society and reduced stigmatization of getting a job or enrolling in apprenticeship. It isrecommended that the management of prisons establishments in Akwa Ibom State should give more time and resources to the prisons entrepreneurship education which contribute more to inmates’entrepreneurial skills acquisition.